THE READABILITY OF REFERENTIAL BOOK FOR EFL STUDENTS IN ENGLISH LANGUAGE EDUCATION DEPARTMENT - Olivia Annatasha Putri; Nunung Nurjati (PROJECT (Professional Journal of English Education), 2023)
Teachers frequently use textbooks as a media resource for instructional education purpose. A capability to understand a textbook being utilized is vital for students. However, the majority of research revealed that the textbooks used did not correspond to the actual level of students. Therefore, this study aimed to investigate the textbook's readability level as well as any potential factors influencing its readability. This research employed a descriptive quantitative method to identify the textbook’s readability using the Miyazaki EFL Readability Index and students' judgments, as well as providing its readability factors. This study’s object included the Morphology textbook, and 36 English Language Education Department students batch 2021 at University of PGRI Adi Buana Surabaya. The first finding demonstrated that the textbook's readability using the Miyazaki EFL Readability Index had a very difficult readability level and best suited for graduate university students. The second finding showed that there were 68.52% of students or 25 students agree that the textbook was difficult to read. The third findings indicated that the percentage of factors affecting the textbook’s readability was 66.67% including the influence of reader factors (22.22%) and text factors (44.44%).